Leading schools of excellence and equity : closing achievement gaps via academic optimism : exploring best practices and documenting effective strategies - Brown, Kathleen M. (Emerald Publishing Limited : Information Age Pub., 2010)
The purpose of this empirical inquiry of state-recognized "Honor Schools of Excellence" was to explore how these schools of distinction are (or are not) promoting and supporting both academic excellence and systemic equity for all students. In Phase One, quantitative data were collected through equity audits to scan for and then document systemic patterns of equity and inequity across multiple domains of student learning and activities within 24 schools. In Phase Two, the 24 schools were ranked, based solely on minority achievement, and then separated into two types of schools, small gap (SG) schools and large gap (LG) schools. Through site visits (n=16) and the use of semi-structured interviews with principals, assistant principals, teachers, and parent leaders (n=80), qualitative data were then collected to document best practices and effective strategies that principals use to confront and change past practices anchored in open and residual racism and class discrimination. The data were analyzed through the theoretical framework of academic optimism.Three differences between the SG schools and the LG schools were found (encouraging academic achievement, offering instructional feedback, and expecting excellence). To truly honor excellence, we need to embrace equity. As such, in schools where principals support, model, and monitor a teamwork approach, a balanced approach, a strong sense of purpose, and an insistent disposition to assure that all students are served well and that all are encouraged to perform at their highest level, the outcomes of interest are better.